A Survey of different decoding schemes for LDPC block codes (International Journal of Engineering and Computer Science, 2015)
Low-density Parity-check (LDPC) code a very promising near-optimal error correction code(ECC), is being widely considered in next generation industry standards. In this paper, two simple iterative low complexity algorithms for decoding LDPC codes have been explained. These algorithms are implemented using real additions only and also not dependent on power spectral density. The survey paper provides fundamentals in the design of LDPC codes. Decoding algorithms used for LDPC codes require large amounts of data to be processed in a short time. LDPC codes are a special type of error correcting codes that is known for their good decoding performance and high throughput.